A genome-wide analysis of Escherichia coli responses to fosfomycin using TraDIS-Xpress reveals novel roles for phosphonate degradation and phosphate transport systems. (5th August 2020) - Turner, A Keith; Yasir, Muhammad; Bastkowski, Sarah; Telatin, Andrea; Page, Andrew J; Charles, Ian G; Webber, Mark A
Abstract: Background: Fosfomycin is an antibiotic that has seen a revival in use due to its unique mechanism of action and efficacy against isolates resistant to many other antibiotics. In Escherichia coli, fosfomycin often selects for loss-of-function mutations within the genes encoding the sugar importers, GlpT and UhpT. There has, however, not been a genome-wide analysis of the basis for fosfomycin susceptibility reported to date. Methods: Here we used TraDIS- Xpress, a high-density transposon mutagenesis approach, to assay the role of all genes in E. coli involved in fosfomycin susceptibility. Results: The data confirmed known fosfomycin susceptibility mechanisms and identified new ones. The assay was able to identify domains within proteins of importance and revealed essential genes with roles in fosfomycin susceptibility based on expression changes. Novel mechanisms of fosfomycin susceptibility that were identified included those involved in glucose metabolism and phosphonate catabolism ( phnC-M ), and the phosphate importer, PstSACB. The impact of these genes on fosfomycin susceptibility was validated by measuring the susceptibility of defined inactivation mutants. Conclusions: This work reveals a wider set of genes that contribute to fosfomycin susceptibility, including core sugar metabolism genes and two systems involved in phosphate uptake and metabolism previously unrecognized as having a role in fosfomycin susceptibility.